Strategi Diplomasi Perdagangan Dan Investasi Menuju Indonesia Emas 2045 - Maimunah Maimunah; Muliahadi Tumagor; Suwito Suwito (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Due to the tendency to depend on certain economic sectors in an effort to support Indonesia Emas 2045 through trade and investment diplomacy. In addition, there is the phenomenon of global economic uncertainty, such as trade wars, geopolitical instability, and currency fluctuations. This research aims to find out how trade and investment diplomacy strategies achieve the goal of the Golden Indonesia 2045. The research method used is the Literature Method, the results of the study concluded that the strategy of trade and investment diplomacy towards golden Indonesia 2045 is by strengthening bilateral and multilateral relations, opening new market access, providing trade and investment facilitation, conducting investment promotions and trade fairs, increasing infrastructure development, risk management and legal stability, strengthening leading sectors, education and human resource development, innovation and technology development, empowering SMEs, empowering local communities and sustainability and the environment.